Strength characteristics of soda waste treated with fly ash and lime - Kou, Hai-Lei
Soda waste is a kind of industrial waste when traditional technology of soda production is adopted. The soda waste cannot be directly used as engineering soil as its low strength. However, it can be used after be mixed with other materials. In this paper, chemical materials such as fly ash and lime are used to be mixed with soda waste. The strength characteristics of soda mixtures with different ratio are studied in detail. Compaction test and unconfined compressive test are conducted respectively to assess the feasibility of these two materials. Based on test results, the mechanical properties of soda mixtures with different ratios of fly ash and lime are discussed. It is indicated that the microstructure of soda waste is similar with soil and the particle size distribution is well to mix with other materials to be used as engineering soil. The optimal ratio of soda waste and fly ash is 7:3 while the ratio is 7 % for soda waste and lime. Using the optimal ratio, the unconfined compression strength of fly ash treated soda and lime treated soda after 14 curing days is 6.5 and 6.1 times of pure soda respectively.